2021
DOI: 10.3390/ani11030890
|View full text |Cite
|
Sign up to set email alerts
|

Socialization in Commercial Breeding Kennels: The Use of Novel Stimuli to Measure Social and Non-Social Fear in Dogs

Abstract: Understanding the behavioral welfare of dogs in commercial breeding kennels (CBKs) is important for improving breeders’ management practices as well as dog welfare. In the current study, breeding dogs from CBKs were exposed to novel stimuli to evaluate their behavioral responses, with emphasis on indicators of fear. Subjects were presented with a standard stranger-approach test, a traffic cone, and a realistic dog statue. Sixty dogs were exposed to the three stimuli and behavioral responses were scored using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Often, dogs are turned out in exercise yards in large groups, and they are often group-housed. These results also align with previous studies where a fake dog was used in behavioral assessments and a higher occurrence of social behaviors was recorded compared to other inanimate objects not resembling a conspecific [ 13 , 21 , 22 ]. The responses to exposure to these different objects loaded together in a single behavioral category that was labelled boldness.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Often, dogs are turned out in exercise yards in large groups, and they are often group-housed. These results also align with previous studies where a fake dog was used in behavioral assessments and a higher occurrence of social behaviors was recorded compared to other inanimate objects not resembling a conspecific [ 13 , 21 , 22 ]. The responses to exposure to these different objects loaded together in a single behavioral category that was labelled boldness.…”
Section: Discussionsupporting
confidence: 91%
“…Training and adult social interactions were less common. A moderate proportion of dogs showed fearful responses toward either social or non-social stimuli, confirming previous findings from this population of dogs [ 2 , 11 , 13 ]. Factors such as sex, social housing, and the number of dogs per caretaker ratio appeared to have an effect on the in-kennel behavior and health scores of the dogs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, the presentation of the artificial dog was used as a proxy measure of dogs' sociability, but the EFA revealed that this stimulus was responded to similarly to other novel objects presented. However, exploratory analysis using a more refined ethogram suggests that the dogs were actually reacting significantly differently to the artificial dog than, for example, the cone, in terms of types and frequencies of behaviors displayed [44]. When interacting with the artificial dog, our subjects showed less fear and more social behaviors (i.e., behaviors shown when interacting with a conspecific such as approaching with a low or a high body posture, increased duration of sniffing) than when introduced to the plastic cone [44].…”
Section: Construct Validitymentioning
confidence: 99%
“…However, exploratory analysis using a more refined ethogram suggests that the dogs were actually reacting significantly differently to the artificial dog than, for example, the cone, in terms of types and frequencies of behaviors displayed [44]. When interacting with the artificial dog, our subjects showed less fear and more social behaviors (i.e., behaviors shown when interacting with a conspecific such as approaching with a low or a high body posture, increased duration of sniffing) than when introduced to the plastic cone [44]. It is possible that the scoring system used here was unable to capture qualitative differences.…”
Section: Construct Validitymentioning
confidence: 99%